2021
DOI: 10.3892/ijo.2021.5265
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin may inhibit the development of cancer via its immunostimulatory and immunomodulatory activities

Abstract: Lactoferrin (Lf) is secreted by ectodermal tissue and has a structure similar to that of transferrin. Although Lf seems to be multifunctional, its main function is related to the natural defense system of mammals. The present review aims to highlight the major actions of Lf, including the regulation of cell growth, the inhibition of toxic compound formation, the removal of harmful free radicals and its important role in immune response regulation. Moreover, Lf has antibacterial, antiviral, antioxidant, antican… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 111 publications
0
10
0
Order By: Relevance
“…Recent studies have confirmed that LF has antitumor, antibacterial, anti‐inflammatory, and immunomodulatory effects. In the antitumor effect, LF can cause damage to different cancer cells and control the proliferation, survival, migration, and invasion of cancer cells 10,11 . In addition, LF interacts with receptors that are overexpressed on the surface of most cancer cells, such as transferrin receptor (TFR), low‐density lipoprotein (LDL), and low‐density lipoprotein receptor‐related protein (LRP), and is highly selective for cancer cells 18–20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have confirmed that LF has antitumor, antibacterial, anti‐inflammatory, and immunomodulatory effects. In the antitumor effect, LF can cause damage to different cancer cells and control the proliferation, survival, migration, and invasion of cancer cells 10,11 . In addition, LF interacts with receptors that are overexpressed on the surface of most cancer cells, such as transferrin receptor (TFR), low‐density lipoprotein (LDL), and low‐density lipoprotein receptor‐related protein (LRP), and is highly selective for cancer cells 18–20 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, as a multifunctional protein, LF has significant antitumor activity, and its potential application in cancer therapy is of great interest. Previous studies have demonstrated that LF has potent cytotoxic effects in tumors, such as breast, lung, colon, and glioma, activating significant antigrowth signals with functions such as controlling tumor proliferation, survival, migration, and invasion aspects 10,11 . In a randomized controlled phase II clinical trial, patients with advanced nonsmall cell lung cancer who received oral recombinant human LF showed significantly improved tumor progression compared to placebo, and the overall survival of patients was increased by nearly 65% 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Elevated fecal lactoferrin levels signify an increased mucosal immune response to food or bacterial antigens and may indicate a chronic state of inflammatory gastrointestinal disease. If this is the case, a further diagnosis is recommended [ 49 , 52 , 53 , 54 ].…”
Section: Inflammatory Bowel Diseases (Ibd)mentioning
confidence: 99%
“…Interestingly, a crosstalk has been demonstrated between the p53 pathway and lactoferrin ( 46 ), and both proteins are components of the tears. Together, they might represent a natural barrier against the development of tumors in the anterior surface of the eye ( 56 ), as well as against infections, and in particular against SARS-CoV-2 ( 57 , 58 ).…”
Section: Mdm2 and P53 Expression In Healthy Ocular Tissuesmentioning
confidence: 99%